Analisis Kausalitas Suku Bunga Nilai Tukar dan Inflasi di Indonesia Tahun 1994-2023 Menggunakan Model VECM - Silvi Trimanda Yolanda; M. Afdal Samsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the causal relationship between interest rates, exchange rates, and inflation in Indonesia during the period 1994–2023 using the Vector Error Correction Model (VECM) approach. The data used are monthly time series secondary data obtained from the World Bank. The Johansen cointegration test results indicate a long-term relationship among the three variables. However, the Granger causality test finds no significant short-term causal relationship. The VECM estimation reveals that inflation is the most responsive variable in correcting long-term disequilibrium, while the exchange rate plays a dominant role in influencing both inflation and interest rates. The Impulse Response Function and Variance Decomposition results indicate that these variables interact dynamically, especially in the medium to long term. These findings highlight the importance of exchange rate stabilization and enhancing the effectiveness of monetary policy to maintain macroeconomic stability in Indonesia.